TERAPI BENSON UNTUK PENURUNAN NYERI RHEUMATOID ARTHRITIS LANSIA - Fatsiwi Nunik Andari; Reska Ayu Santri; Nurhayati Nurhayati (Jurnal Vokasi Keperawatan (JVK), 2021)
Rheumatoid Arthritis is a long-term condition that causes pain, swelling and stiffness in the joints, especially in the hands, feet, and wrists. Benson therapy is one of the pain reliefs of rhumatoid arthritis. The aim of this study was to examine the effect of benson therapy to reduce Rheumatoid arthritis pain in elderly patients at Nursing Home of Tersna Werdha in Bengkulu. This research was a quantitative study with a quasi-experimental design. The results of the dependent t-test showed the p-value of  0.000 (p <0.05), it means that there was a significant effect of benson therapy in reducing rheumatoid arthritis pain.